2015
DOI: 10.1155/2015/902084
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Atlantic Contributions to Strong Rainfall Variability Along the Northeast Brazilian Coast

Abstract: Tropical Atlantic (TA) Ocean-atmosphere interactions and their contributions to strong variability of rainfall along the Northeast Brazilian (NEB) coast were investigated for the years 1974–2008. The core rainy seasons of March-April and June-July were identified for Fortaleza (northern NEB; NNEB) and Recife (eastern NEB; ENEB), respectively. Lagged linear regressions between sea surface temperature (SST) and pseudo wind stress (PWS) anomalies over the entire TA and strong rainfall anomalies at Fortaleza and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 40 publications
8
59
0
4
Order By: Relevance
“…Rainfall variability due to the other systems such as the easterly wave disturbances (EWs) and upper tropospheric cyclonic vortices (TCVs) is out of the scope of the present analysis. The EWs affect eastern NEB during austral winter (Yamazaki and Rao, 1977;Kouadio et al, 2012;Hounsou-Gbo et al, 2015) and the TCVs are more common during austral summer and affect most of NEB (Kousky and Gan, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall variability due to the other systems such as the easterly wave disturbances (EWs) and upper tropospheric cyclonic vortices (TCVs) is out of the scope of the present analysis. The EWs affect eastern NEB during austral winter (Yamazaki and Rao, 1977;Kouadio et al, 2012;Hounsou-Gbo et al, 2015) and the TCVs are more common during austral summer and affect most of NEB (Kousky and Gan, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…When these disturbances propagate toward the eastern NEB they can generate large rainfall amounts specially over the eastern coastal areas (e.g. Gomes et al, 2015;Hounsou-gbo et al, 2015;Kouadio et al, 2012). Rao et al (1993) found that the seasonal variation of the intensity and position of the subtropical high in the South Atlantic Ocean modulates coastal winds during the fall and winter.…”
Section: Factors Influencing Precipitation Regimesmentioning
confidence: 99%
“…These climate modes are of importance especially due to their impact on precipitation over the adjacent continents. Variations in rainfall over Northeast Brazil are closely related to SST variability in the tropical Atlantic Ocean (e.g., Hounsou-Gbo et al, 2015). In particular SST variability in the ACT is related to the West African Monsoon (Brandt, Caniaux, et al, 2011;Caniaux et al, 2011), and Benguela Niños have an impact on rainfall over southwestern Africa and coastal central Africa (Lutz et al, 2015;Reason & Rouault, 2006;Rouault et al, 2009).…”
Section: 1029/2018ea000428mentioning
confidence: 99%